Kinetics and Thermodynamics of Thermal Inactivation of Peroxidase from Cauliflower (Brassica oleracea L. var. botrytis) Leaves - Kalsoom, Umme; Nawaz Bhatti, Haq; Ahmad Bhatti, Ijaz; Asgher, Muhammad (Asian Journal of Chemistry, 2010)
Peroxidase from leaves of cauliflower (Brassica oleracea L. var. botrytis) was isolated and partially purified by means of ammonium sulfate precipitation. The enzyme exhibited maximum activity at pH 5.5 and temperature 50 °C. The values of Km and Vmax for guaiacol oxidation were 7.14 mM and 204.1 μmol/min, respectively. Thermal inactivation of the peroxidase was carried out in aqueous solution at temperatures ranging from 60 to 80 °C. The enthalpy (DHº) and free energy (DGº) of thermal denaturation of cauliflower peroxidase were 89.60 and 109.73 k J/mol, respectively at 80 ºC. Metals like Hg2+ slightly inhibited the peroxidase activity while Zn2+, Mn2+, Cr3+, Ni2+, Co2+ and Ca2+ have no effect on enzyme activity. The effects of some surfactants and commercial detergents have also been investigated. The thermal stability makes cauliflower peroxidase an alternative to horseradish peroxidase in commercial applications.